2019
DOI: 10.1007/s40199-019-00268-1
|View full text |Cite
|
Sign up to set email alerts
|

Providing a framework for assessment of the access to medicine

Abstract: Objective Improving access to effective and safe medicines is one of the major goals of all health systems. To achieve this goal, assessment is a fundamental phase of national medicine programs for access improvement. Collecting and compiling applicable indicators and impart a comprehensive framework for assessing access to medicine, are the aims of this study. Methods To investigate the published materials on access to medicines framework or indicators, a literature review with a systematic search was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…They considered multiple levels of organization from the household level to the international context (Fig 1). Among a set of extant access to medicines frameworks [6][7][8][9][10][11][12][13][14][15] this framework (Bigdeli et al's framework [9]) was found to be the most comprehensive conception yet of what access to medicine entails. Therefore, this framework's domains formed the basis of our coding scheme outlined in S1 Data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They considered multiple levels of organization from the household level to the international context (Fig 1). Among a set of extant access to medicines frameworks [6][7][8][9][10][11][12][13][14][15] this framework (Bigdeli et al's framework [9]) was found to be the most comprehensive conception yet of what access to medicine entails. Therefore, this framework's domains formed the basis of our coding scheme outlined in S1 Data.…”
Section: Discussionmentioning
confidence: 99%
“…These diabetes policies must be attentive to factors affecting access to medicines for diabetes patients because the key to effective diabetes management includes adherence to insulin and oral medicines [6,7]. Among the several frameworks conceptualising the access to medicines and health technologies [6][7][8][9][10][11][12][13][14][15], two of the most recently published [6,7] relate specifically to medicines for cardiovascular diseases and diabetes, suggesting the recognition of the unique salience of diabetes and cardiovascular diseases. 'Access to medicine' is defined here as the multi-dimensional construct that characterises the degree to which quality and safe medicines are available, affordable, accessible and acceptable in a timely manner to those needing them [6][7][8][9][10][11][12][13][14][15].…”
Section: Diabetes In Sub-saharan Africa and The Importance Of Patient...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pursuing leads on potentially relevant authors and publications, based on personal communications from colleagues, also proved useful for identifying published ATM frameworks. These works 48 50 were identified this way.…”
Section: Methodsmentioning
confidence: 99%
“…Afzali et al 48 To provide an evidence-based framework for evaluating access to medicine using a system approach, with indicators disaggregated by inputs, outputs and outcomes Information provision about benefits, side effects, use of medicines at the point of dispensing is conceptualised as one of the indicators of access.…”
mentioning
confidence: 99%